The Myths and Beliefs Surrounding Mappaenre Bunge: Disease, Tradition, and Social Impact in Bugis Society - Mutmainna Mutmainna; Nursyam Aisyah Nursyam; Asfar Asfar; Asfar Asfar; Nurannisa Nurannisa; Sukmawati Sukmawati; Rijal Rijal (Universitas Andalas, 2024)
The Mappaenre Bunge tradition as a ritual that has been going on for generations has deep meaning for the Bugis people. The community believes that by carrying out this tradition, they will establish a harmonious relationship with their ancestors and the universe. People think that if this tradition is not implemented, then people will be affected by disease. The aim of this research is to explore the Mappaenre Bunge tradition in Bugis community culture; examine people's views on counter-myths in the Mappaenre Bunge tradition in Bugis society; and reveal the influence of the Mappaenre Bunge tradition on the emergence of disease in the Bugis tribe. The research methods used are historical methods and phenomenological methods. The historical method is used to collect data about the origins and development of the Mappaenre Bunge tradition, while the phenomenological method is used to understand the experience and meaning of the Mappaenre Bunge tradition for the Bugis community. The results of this research reveal the aim of this research, namely to find out the origins of the emergence of the Mappaenre Bunge tradition; found 6 myths and 3 counter-myths; The myths present in the Tappale Village Community are stronger than the counter-myths.